2018
DOI: 10.1152/ajprenal.00202.2018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of renal and cardiovascular protection mechanisms of SGLT2 inhibitors: model-based analysis of clinical data

Abstract: The mechanisms of cardiovascular and renal protection observed in clinical trials of SGLT2 inhibitors (SGLT2i) are incompletely understood and likely multifactorial, including natriuretic, diuretic, and antihypertensive effects, glomerular pressure reduction, and lowering of plasma and interstitial fluid volume. To quantitatively evaluate the contribution of proposed SGLT2i mechanisms of action on changes in renal hemodynamics and volume status, we coupled a mathematical model of renal function and volume home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
73
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 45 publications
9
73
0
2
Order By: Relevance
“…14 In clinical trials, the use of SGLT2 inhibitors has been shown to reduce the quantity of epicardial adipose tissue (independently of effect on body weight), [35][36][37] and these drugs ameliorate the inflammation of adipose tissue surrounding the heart and great vessels 38,39 and the associated abnormalities of cardiac filling and aortic distensibility in both experimental and clinical HFpEF. 18,[40][41][42] Furthermore, SGLT2 inhibitors act to inhibit sodium reabsorption in the proximal renal tubules, in which the majority of renal sodium retention occurs [43][44][45] ; this action explains the marked reduction in plasma and/or interstitial volume and haemoconcentration seen in randomized controlled trials in type 2 diabetes. 25,46 Moreover, SGLT2 inhibitors can attenuate renal inflammation and fibrosis.…”
Section: Sample Size Calculations and Study Conductmentioning
confidence: 99%
“…14 In clinical trials, the use of SGLT2 inhibitors has been shown to reduce the quantity of epicardial adipose tissue (independently of effect on body weight), [35][36][37] and these drugs ameliorate the inflammation of adipose tissue surrounding the heart and great vessels 38,39 and the associated abnormalities of cardiac filling and aortic distensibility in both experimental and clinical HFpEF. 18,[40][41][42] Furthermore, SGLT2 inhibitors act to inhibit sodium reabsorption in the proximal renal tubules, in which the majority of renal sodium retention occurs [43][44][45] ; this action explains the marked reduction in plasma and/or interstitial volume and haemoconcentration seen in randomized controlled trials in type 2 diabetes. 25,46 Moreover, SGLT2 inhibitors can attenuate renal inflammation and fibrosis.…”
Section: Sample Size Calculations and Study Conductmentioning
confidence: 99%
“…We expected that this analysis would improve our understanding of the renal benefits of SGLT2 inhibition but did not anticipate, initially, insight into the protective effects in heart failure. However, this analysis provided, ultimately, mechanistic insights into both, as we have described previously . We continue to use the model to further explore the cardiac effects of SGLT2 inhibition.…”
Section: Case Study 1: Cardio‐renal Drug‐disease Qsp Modeling Enabledmentioning
confidence: 70%
“…In addition, prospective simulations with the model indicated that SGLT2 inhibition reduces interstitial fluid volume to a greater extent than blood volume—an experimentally testable hypothesis that may explain the positive effects of these drugs on heart failure hospitalization. These results were communicated through both presentations and peer‐reviewed publications . Importantly, this differential volume mechanism lent decision support to development teams weighing the hypothesis that SGLT2 inhibitors would demonstrate clinical benefit in heart failure and slowing renal disease progression, both indications now pursued in several outcomes trials.…”
Section: Case Study 1: Cardio‐renal Drug‐disease Qsp Modeling Enabledmentioning
confidence: 96%
See 2 more Smart Citations